Hubungan Antara Komorbiditas Dengan Derajat Keparahan Infeksi Covid-19 Di Rumah Sakit Sanjiwani Gianyar - Anak Agung Gede Budhitresna; Ni Luh Putu Eka Kartika Sari; I Nyoman Arep Kusuma Negara (Aesculapius Medical Journal, 2022)
COVID-19 is the leading cause of respiratory disease outbreaks worldwide. 30,949,804 cases of COVID19 have been confirmed since September 21, 2020, and 959,116 people have died worldwide. There are still differences of opinion regarding several diseases that underlie the worsening condition of COVID-19 patients. This study aims to determine the relationship between comorbidities and the severity of COVID-19 infection at the Sanjiwani Hospital. The research method used is analytic observational with a cross-sectional approach, by analyzing secondary data in the form of medical records. A sample of 164 people who have met the exclusion and inclusion criteria, were obtained using the Consecutive sampling technique. Data were analyzed by SPSS. The chi-square test and multiple logistic regression were used to determine the relationship among comorbidities and the severity of COVID-19 infection. Based on the results of multiple logistic regression, the comorbid factors for the severity of COVID-19 infection were hypertension, type 2 diabetes mellitus, COPD, pulmonary TB, chronic heart failure. The most dominant comorbid factor was pulmonary TB (Exp(B)=12,566 95% CI; 3,560 - 44,353).